The Economic Consequences and Impact of the COVID-19 Pandemic on the Global Economy - Sargsyan, Karen; Sargsyan, Armen (ՀՀ ԳԱԱ)
Due to the coronavirus pandemic, the world economy entered another phase of crisis at a fairly rapid pace from the beginning of 2020. The COVID-19 pandemic has affected more than 50 million people in almost every country in the world. Because of the crisis caused by COVID-19, governments around the world were operating in complete uncertainty, facing a difficult situation. with the choice of compromises, taking into account the existing health, economic and social challenges. By the spring of 2020, more than half of the world's population had been restricted by strong restraint measures. The widespread coronavirus pandemic, in addition to a health and human tragedy, caused the most serious economic crisis in the world since World War II. The main feature of the pandemic crisis was the emergence of a double shock in terms of "supply" and "demand". It was truly unprecedented for the world economy, which led to unusually large economic shocks and unpredictability of future developments. Կորոնավիրուսային համավարակի պատճառով համաշխարհային տնտեսությունը 2020 թվականի սկզբից բավականին արագ տեմպերով թևակոխեց մեկ այլ ճգնաժամի փուլ: COVID-19 համավարակը ազդել է աշխարհի գրեթե բոլոր երկրների և ավելի քան 50 միլիոն մարդու վրա: COVID-19-ի առաջացրած ճգնաժամի պատճառով կառավարություններն ամբողջ աշխարհի մակարդակով գործում էին լիակատար անորոշության պայմաններում՝ բախվելով դժվարին փոխզիջումների ընտրությանը՝ հաշվի առնելով առկա առողջապահական, տնտեսական և սոցիալական մարտահրավերները: 2020 թվականի գարնան դրությամբ աշխարհի բնակչության կեսից ավելին հայտնվել էր սահմանափակումների մեջ՝ կիրառված ուժեղ զսպման միջոցառումների արդյունքում: Հանրային լայն ընկալմամբ՝ կորոնավիրուսային համավարակը, առողջապահական և մարդկային ողբերգությունից բացի, երկրորդ համաշխարհային պատերազմից ի վեր ամենալուրջ տնտեսական ճգնաժամ էր առաջացրել աշխարհում: Из-за эпидемии коронавируса мировая экономика с начала 2020 года достаточно быстрыми темпами вошла в очередную фазу кризиса. Эпидемия COVID-19 затронула более 50 миллионов человек почти во всех странах мира. Из-за кризиса, вызванного COVID-19, правительства по всему миру работали в условиях полной неопределенности, столкнувшись со сложной ситуацией с выбором компромиссов с учетом существующих медицинских, экономических и социальных проблем. К весне 2020 года более половины населения планеты были охвачены жесткими ограничительными мерами. Широкомасштабная эпидемия коронавируса, помимо медицинской и человеческой трагедии, стала причиной самого серьезного экономического кризиса в мире со времен Второй мировой войны.
Keywords: Social and Humanitarian Sciences